Spirometra infection in a captive Samar cobra (Naja samarensis) in the United States: An imported case? - Guilherme G. Verocai; Tatiani V. Harvey; Caroline Sobotyk; Rachel Ellerd Siu; Matthew Kulpa; Maren Connolly (International Journal for Parasitology: Parasites and Wildlife, 2023)
We report a case of Spirometra infection in a Samar cobra (Naja samarensis) imported from the Philippines, belonging to a zoological collection in the southern United States. Under a poor post-surgical prognosis, the snake was euthanized, and at necropsy plerocercoids of a Diphyllobotriidea were found in its subcutaneous tissues and musculature. Molecular and phylogenetic analyses of the complete cytochrome oxidase c subunit I (cox1) gene of the mitochondrial DNA confirmed that the isolate belonged to the genus Spirometra and was closely related to Spirometra mansoni isolates from Asian countries (bootstrap support = 99.4%). Considering the origin and clinical history and handling of the animal, the snake probably arrived infected in America. We suggest the inclusion of diagnostic imaging in the investigation of sparganosis in research and disease surveillance protocols applied in the pre- and post-quarantine period to asymptomatic animals imported from endemic areas.